Students’ Perceptions towards The Utilization Of “Whatsapp” for Vocabulary Teaching and Learning - Wijayanti, Anita; Gunawan, Yohanes Bambang (Ahmad Dahlan Journal of English Studies, 2018)
Society has enjoyed the ease of communication afforded by “Whatsapp”, a popular freeware and cross-platform communication application. “Whatsapp”’s popularity has invited educators to experiment with it in various ways to shore up education. This study was conducted to describe students’ perceptions on the use of “Whatsapp” for teaching and learning vocabulary. A vocabulary virtual class in the form of a “Whatsapp” group where students needed to enroll was created for that purpose. This virtual class exempted the students from physically attending the physical class as it enabled students to remotely attend the class. Teaching and learning methods of vocabulary in the virtual class included using pictures, translation, and sentence construction. At the end of the class, the students were to inform the researchers about their perceptions of the virtual class. This study used a descriptive qualitative method. Data was collected through a paper-based questionnaire, which was distributed to all students in a face-to-face class, a session taking place two days prior to the research. The virtual vocabulary class that the researchers administered overall received positive feedbacks from the learners. However, teaching and learning vocabulary using “Whatsapp” also had its own drawback.